THE IMPACT OF ETHNIC CONFLICTS ON THE QUALITY OF LIFE AND HUMAN HEALTH: A CASE STUDY OF THE KOSOVO AND METOHIJA (Heritage, 2023)
The subject of this research is the assessment of the influence of ethnic conflicts on the quality of life and health of people. The aim of the research is to identify and highlight the influence of conflicts on human health in the environments which were exposed to those conflicts at the end of the 20th and the beginning of the 21st century. The research was conducted in Kosovo and Metohija. The research covered all ethnic groups of the population that were treated in health care institutions belonging to the system of the Republic of Serbia (Health Centers in Kosovska Mitrovica and Gračanica). The ways in which trauma, gender, age, marriage and household size affect the fear of violence were investigated. The differences between types of fear were stated, i.e. it was investigated whether respondents were more concerned about their property or their personal safety
Keywords: Ethnic conflicts, Quality of life, Consequences, Human health, Kosovo and Metohija